Perceive idea of e-learning adoption upon UiTM student/ Franklin Giman - Giman, Franklin (2016)
In this research study e-learning is learning utilizing electronic technologies to access educational curriculum outside of a traditional classroom. In distance education courses, the instruction is prepared and packed days, weeks, months, or a year before the act of learning by the student. This time difference creates an environment quite distinct from the typical face-to-face instruction of the college classroom where the teaching and learning take place in the same time frame and with the professor and student in the same room. Besides that, in era of information technology the availability of interactive technology has enabled e-learning to move from textbook or classroom metaphor to more experimental learning models.